The Middle Jurassic dinoflagellate cyst biostratigraphy of the Lusitanian Basin, Portugal [Resumo] - Correia, Vânia (2022)
ABSTRACT: A mainly Middle Jurassic composite succession with 129 samples was examined palynologically. This spans the Toarcian–Aalenian transition to the lowermost Bathonian, exposed at Cabo Mondego (includes the GSSP and the ASSP for the Bajocian and Bathonian stages respectively) and São Gião in the northern Lusitanian Basin, western Portugal. The main goal was to establish a biostratigraphical scheme based on dinoflagellate cysts bioevents.